2017
DOI: 10.1007/s00421-017-3594-0
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise increases lactoferrin, but decreases lysozyme in salivary granulocytes

Abstract: Acute running resulted in an increased Lac concentration which could lead to a decrease in inflammation, adding further evidence of the anti-inflammatory effects of exercise. Conversely, the exercise-associated decrease of intracellular Lys content could be the cause of increased Lys in exocrine solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Fielding et al [22] also stated that levels of lactoferrin also increased following a 2-hour submaximal cycle followed by a bout of eccentric resistance exercise. Similarly, a previous study by Gillum et al [12] found that exercise increased the concentration of salivary AMPs including lactoferrin concentration from pre to post-exercise with running at 75% VO2max for 45 minutes. However, a separate study found that salivary lactoferrin concentrations decreased during a training season in elite rowers [23].…”
Section: Salivary Lactoferrin Concentration and Secretion Ratesupporting
confidence: 53%
See 1 more Smart Citation
“…Fielding et al [22] also stated that levels of lactoferrin also increased following a 2-hour submaximal cycle followed by a bout of eccentric resistance exercise. Similarly, a previous study by Gillum et al [12] found that exercise increased the concentration of salivary AMPs including lactoferrin concentration from pre to post-exercise with running at 75% VO2max for 45 minutes. However, a separate study found that salivary lactoferrin concentrations decreased during a training season in elite rowers [23].…”
Section: Salivary Lactoferrin Concentration and Secretion Ratesupporting
confidence: 53%
“…Sample size was calculated by using PS Software. Based on a study which was carried out by Gillium et al [12], the power of the study was set at 80% with 95% confident interval, the standard deviation (σ) observed was 750 (units/ml) of lactoferrin concentration, and difference in population mean (δ) was set at 1035 (units/ml) of lactoferrin concentration. The calculated sample size was 9 participants per group.…”
Section: Methodsmentioning
confidence: 99%
“…Although SIgA is considered as the main agent in the mucosa, most recently, the importance of antibacterial peptides in the protection of airway mucosa has been recognized [41,42]. Higher levels of these immunological agents can be found in physically active people [43,44,45] leading to greater protection, which decreases the incidence of upper respiratory tract infection in this population [42].…”
Section: Discussionmentioning
confidence: 99%
“…In past, one of them -salivary lysozyme was examined in connections to both, psychological and physical stress conditions and appeared to be inversely correlated to subjectively perceived level of psychological stress (Perera et al, 1997;Perera et al, 1998). On the other hand, acute moderate or high intensity exercise has been shown to increase salivary lysozyme levels (Allgrove et al, 2008;Gillum et al, 2017a;Gillum et al, 2017b) in contrast to prolonged intense training causing its decrease in saliva. For instance, in work published by West and coworkers (West et al, 2010) elite rowers had approximately half the concentration of salivary lysozyme and lactoferrin than non-exercising control subjects over a 5-month training season (West et al, 2010).…”
Section: Introductionmentioning
confidence: 99%